Manual on wound care after open-window thoracostomy (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: To produce and validate a manual on wound care after open-window thoracostomy for healthcare professionals. Methods: This is an experience report. Initially, articles in Portuguese, Spanish and English were selected from 2010 to 2018 in the Cochrane, SciELO, LILACS, PubMed and Google Academic databases and search sites for the development of the material. The following descriptors were used: “thoracotomy”, “thoracostomies”, “thoracic cavity”, “pleura”, “pleural cavity”, “injuries and lesions”. After consultation, the text was prepared, followed by illustrations and layout design. The completed manuscript was sent to experts for validation. The content validity index (CVI) was used to validate the manual. Results: The manual developed has thirty-six pages and seven chapters with the following themes: introduction, wound care after open-window thoracostomy, wound cleansing/debridement, dressings, care record, final considerations, and bibliography. Conclusion: It was possible to develop and validate a manual on wound care after open-window thoracostomy for the consultation of health professionals.